6x-2x+6=36

Simple and best practice solution for 6x-2x+6=36 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6x-2x+6=36 equation:


Simplifying
6x + -2x + 6 = 36

Reorder the terms:
6 + 6x + -2x = 36

Combine like terms: 6x + -2x = 4x
6 + 4x = 36

Solving
6 + 4x = 36

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6' to each side of the equation.
6 + -6 + 4x = 36 + -6

Combine like terms: 6 + -6 = 0
0 + 4x = 36 + -6
4x = 36 + -6

Combine like terms: 36 + -6 = 30
4x = 30

Divide each side by '4'.
x = 7.5

Simplifying
x = 7.5

See similar equations:

| 12x-5=7x+5 | | 3x+4=7x+8 | | y^4-y^2-72=0 | | 2p^2+5p=8 | | 7x-18=y+3 | | 11k+3=k+17 | | 7x-x=42 | | 7(y-3)=35 | | 2(3x-7)=2-10x | | -8=32-5x | | 2(4+x)=12 | | 9+7=29+5 | | 3x+12=2x-2 | | 6-7x=4(2x-6) | | 5y=10x+10 | | 6x+11=121-5x | | 8x^2-4x=24 | | 6x+2x=73.2 | | 8y=32 | | 3.5x+0.8=-16.7 | | 93+24k+26k=218 | | 3.5x+0.8=16.7 | | -2x-x+7x= | | 2.6=-0.4x | | 6x+2x=163.2 | | 7x-5x+5= | | 2p^2+6p=5 | | 28+12x=8x-4 | | 1.5x=9.6x+k | | 10x+8=4x+38 | | 3(x+2)=16-x | | x^2+42.25=-13x |

Equations solver categories